Towards an increasingly less foreign school. Links between migrant families and teachers to build an educational alliance - Silvia Sordella (University of Bologna, 2022)
The role of parents in students learning pathways is the subject of many studies that analyze the correlation with academic achievement considering the weight of several variables, including the socio-cultural background of the family. This paper focuses on theoretical and methodological aspects of this educational field and presents some activities to promote the role of parents in children's language education, within the European project NEW ABC. Starting from the various tools used in the research-action project, we will identify some productive areas of collaboration with the foreign families, especially in a task of enhancement of plurilingualism.